Global research trends on platelet-rich plasma for tendon and ligament injuries from the past two decades: A bibliometric and visualized study - Xu, Jie; Du, Wanli; Xue, Xiali; Chen, Meng; Zhou, Wenqi; Luo, Xiaobing (Frontiers in Surgery, 2023)
Background In sports medicine, tendon and ligament injuries are the most prevalent conditions, and with the booming of sports competition, the incidence of sports injuries is gradually increasing, investigating more potent therapeutic options is therefore becoming increasingly crucial. Platelet-rich plasma therapy has gained popularity as an effective and secure treatment in recent years. Currently, a faceted systematic and clear visual analysis is lacking in this research area. Methods The literature related to using platelet-rich plasma to treat ligament and tendon injuries from 2003 to 2022 in the core dataset of the Web of Science database was collected and analyzed visually using Citespace 6.1 software. Research hotspots and development trends were analyzed in terms of high-impact countries or regions, authors, research institutions, keywords, and cited literature. Results The literature comprised a total of 1,827 articles. The annual publication volume of relevant literature has demonstrated a significant development tendency as the field of platelet-rich plasma research for tendon and ligament injuries has heated up in recent years. With 678 papers, the United States came in top place, followed by China with 187 papers. Hosp Special Surg ranked first with 56 papers. The hot research topics analyzed by keywords were tennis elbow, anterior cruciate ligament, rotator cuff repair, achilles tendon, mesenchymal stem cells, guided tissue regeneration, network meta analysis, chronic patellar tendinopathy, and follow up. Conclusion Analysis of the research literature over the past 20 years shows that the United States and China will continue to dominate in terms of volume of publications based on annual volume and trends, with some collaboration among high-impact authors and further collaboration still needed in different countries and institutions. Platelet-rich plasma is widely used in the treatment of tendon ligament injuries. Its clinical efficacy is influenced by a number of factors, the main ones being the inconsistency in the preparation and composition of platelet-rich plasma and its related preparations, and the differences in efficacy due to different activation methods of platelet-rich plasma, as well as factors such as injection time, injection site, administration method, number of administrations, acidity and evaluation methods, In addition, the applicability to different injury diseases remains controversial. In recent years, the molecular biology of platelet-rich plasma for tendon ligament therapy has received increasing attention.